If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+3(-1)/6+(-7)+1=0
We simplify the equation to the form, which is simple to understand
2+3(-1)/6+(-7)+1=0
Reorder the terms in parentheses
2+(-3)/6+(-7)+1=0
Reorder the terms in parentheses
2+(-0.5)+(-7)+1=0
Remove unnecessary parentheses
+2-0.5+(-7+)+1=0
Remove unnecessary parentheses
+2-0.5-7+1=0
We move all terms containing to the left and all other terms to the right.
0=0-2 + 0.5+7-1
We simplify left and right side of the equation.
0=+4.5
0=4.5
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 9x+15=9x-15 | | 7+2s-5=8s+20-4s | | 4600=k(30) | | 4v+23v+28=0 | | 2s+8l=120 | | x^4-5x^3-13x^2-7x=0 | | 14-2(3p+1)=5x-(x+21) | | 14-(-2)=10 | | 85+110+12x-1+11x+5=360 | | x^2-9x+20.45=0 | | x+x+0.0+x+010+0.63=10.28 | | -8(2k-6)=16 | | x=10.4+(9.8)(1.7) | | 3c+23c+40=0 | | 99-99=0 | | 4x-2(-4)=12 | | 2(t-3)+8t=5(2t+3)-11 | | 45s^2+100st+55t^2=0 | | 4(m-3)=3m+5 | | 2(x+3)+xy=4-(x+13)+xy | | -16w^2+36w+70=0 | | -5x-2y=-16 | | 44.59=9g+3.82 | | 1.4t=56 | | 4(-4)-2y=12 | | 1.44g-3=0.60 | | 7x=31+-2y | | 6(5-2g)-3(-p+7)= | | 6(2x+9)=(6x+12) | | 4v^2+24v+27=0 | | -44-6x=-x+16 | | H=-5t^2+80 |